Enantioselective aza-electrophilic dearomatization of naphthalene derivatives - Jun Liu; Haina Liu; Meijuan Zhou; Xiaolong Yu; Gang Zhao; Hongyu Wang (Nature Communications)
Abstract The catalytic asymmetric dearomatization of naphthalenes is a pivotal strategy for generating enantioenriched three-dimensional aliphatic polycycles from flat aromatic precursors. However, achieving such transformations involving electronically unbiased naphthalenes remains a long-standing challenge. Here, we describe a silver-mediated enantioselective aza-electrophilic dearomatization approach that couples readily accessible vinylnaphthalenes in conjunction with azodicarboxylates to afford chiral polyheterocycles via formal [4 + 2] cycloaddition reactions, yielding up to 99% yield and 99 : 1 e.r. Central to the method is the formation of an aziridinium intermediate that facilitates the subsequent dearomatization of naphthalenes. A 100 mmol-scale reaction and the divergent transformation of the products into enantioenriched aliphatic polycycles highlight their synthetic utility. Mechanistic experiments and DFT calculations offer insights into the reaction mechanism and the origin of the observed enantiocontrol outcome.